Complex Failure Simulation of Underinclined Shale Slope Based on Discrete Element Method - Li, Bin; Huang, Da (Earth Sciences Research Journal, 2020)
A landslide occurred in the cut slope located in Chongqing west railway station, this slope belongs to a under-dip shale slope, which means that its bedding dip angle is larger than slope angle and it is comprised of soft rock. Some on-site investigations have been made to explore the deformation characteristics of this slope, the outcome suggested that sliding, buckling and toppling deformation existed at its different parts. To elucidate the complex failure mechanism exhibited by the under-dip slope under the long-term influence of gravity and material deterioration, the discrete element method has been employed in simulations. The simulated failure patterns have proven to be in strong agreement with the actual slope failure. This study suggests that sliding, buckling and toppling occur at different parts of the studied slope in sequence.